2000
DOI: 10.1055/s-2008-1072393
|View full text |Cite
|
Sign up to set email alerts
|

Early Biliary Pseudolithiasis During Ceftriaxone Therapy for Acute Pyelonephritis in Children: A Prospective Study in 34 Children

Abstract: The prolonged biological half-life of Ceftriaxone, allowing once-daily dosing, has contributed to the large diffusion of this third-generation cephalosporin in children. Ceftriaxone is known to induce reversible precipitates in the gallbladder of adults and children. A prospective study was conducted during 1997 in 34 children admitted for the treatment of acute pyelonephritis. Ceftriaxone (intravenous daily single-dose of 50 mg/kg under 2g/day) was initially used. A first gallbladder sonogram, performed befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 11 publications
1
8
0
2
Order By: Relevance
“…13 Our results showed that 29 out of 176 patients (16.48%) who received Ceftriaxone for more than 7days experienced this side effect in their gallbladder. Bonnet et al (2000) in a prospective clinical study on 34 children confirmed Ceftriaxone-induced biliary stone in 15% of participants.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…13 Our results showed that 29 out of 176 patients (16.48%) who received Ceftriaxone for more than 7days experienced this side effect in their gallbladder. Bonnet et al (2000) in a prospective clinical study on 34 children confirmed Ceftriaxone-induced biliary stone in 15% of participants.…”
Section: Discussionmentioning
confidence: 91%
“…Although their sample size was very small for determination of prevalence of biliary stone in the population, the obtained results were very similar to the findings of the present study. 16 T A B L E 2 Prevalence of biliary and kidney sludge and stone base on genotype variations CHART 1 Incident of biliary and kidney sludge and stones by sex It was proved that gender plays a significant role in gallbladder diseases. Many studies showed that these disorders are more prevalent in females than males.…”
Section: Discussionmentioning
confidence: 99%
“…Seftriaksonun psödolitiyazis gelişmesindeki altta yatan nedenleri halen tam olarak bilinmemektedir (11,12,16). Seftriaksona bağlı oluşan psödolitiyazisli hastalarda yapılan bir çalışmada bilirubin eliminasyonunda etkili olan UDP Glukuronoziltransferaz'ı kodlayan UGT1A1 geninin önemli bir rolü olduğu gösterilmiştir (17).…”
Section: Discussionunclassified
“…Seftriaksona bağlı oluşan psödolitiyazisli hastalarda yapılan bir çalışmada bilirubin eliminasyonunda etkili olan UDP Glukuronoziltransferaz'ı kodlayan UGT1A1 geninin önemli bir rolü olduğu gösterilmiştir (17). Çok sayıda çalışmada seftriaksona bağlı psödolitiyazis oluşum mekanizmaları aydınlatılmaya çalışılmıştır (16,18). Seftriaksonun karaciğere transportu ve safra kesesine atılımı safra asitlerininki ile aynıdır.…”
Section: Discussionunclassified
“…25 Previous studies about urolithiasis following Ceftriaxone usage had demonstrated that most cases were asymptomatic too. 5,[25][26][27][28] In four of our five nephrolithiasis cases, the renal calculus disappeared in a mean time of 3 weeks. While, one stone persisted up to 9 months after treatment.…”
Section: Nephrolithiasis In Children Receiving Cefotri Ceftriaxone Axonementioning
confidence: 99%